Analysis of the VERNALIZATION-A1 exon-4 polymorphism in polyploid wheat - A. F. Muterko; E. A. Salina (Вавиловский журнал генетики и селекции)
One of the key genes that influence the adaptability of wheat to environments and yield are the VRN1 genes. In recent studies, an association of missense mutations within VERNALIZATION-A1 exon-4 with modulation of quantitative values of such agronomically valuable traits as frost tolerance, vernalization requirement duration and flowering time of wheat was shown. However, these investigations were carried out exclusively in T. aestivum varieties and have not covered other species of polyploid wheat and different VRN-A1 alleles. The earlier studies did not consider more than one copy of VRN-A1 per genome. Furthermore, only recently it was shown that only several SNPs distinguish the VRN-D4 and VRN-A1 genes. In the present study, VRN-A1 exon-4 polymorphism was investigated in 158 accessions of 6 tetraploid and 5 hexaploid wheat species carrying the different VRN-A1 alleles. To identify the VRN-A1 exon-4 haplotypes, a co-dominant marker was designed, based on modulation of the curvature of the DNA molecule. Polymorphism of the VRN-A1 exon-4 was revealed only in hexaploid wheat accessions and was associated with the presence of not less than two copies of VRN-A1 per genome. With the exception of one accession, the mutant type of exon-4 was identified only in combination with the wild type. Furthermore, allele-specific primers were designed to identify the VRN-D4 gene or in order to exclude its impact on the results during analysis of the VRN-A1 haplotypes. By expanding the region being analyzed, additional haplotypes, which are associated with polymorphism of adenine tracts within intron-4, were identified. Haplotype segregation was attained among accessions carrying only intact exon-4 of VRN-A1 and among dominant alleles of this gene. Finally, based on the associations revealed between the VRN-A1 alleles and haplotypes, the new putative dominant VRN-A1 allele (designated Vrn-A1k) carrying a 42-bp insertion within the promoter region was identified in tetraploid wheat of Triticum dicoccum.